2020
DOI: 10.1055/s-0040-1710535
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Thoracic Surgery

Abstract: Enhanced recovery programs (ERPs) aim to reduce psychological and physiological stress related to surgery, and minimize opioid use. This article describes the tenets of enhanced recovery, the guidelines for ERP in lung surgery, and the University of Virginia experience with developing and implementing a program. The impact of these strategies on short-term patient outcomes and potential long-term benefits including influence on lung cancer-specific outcomes are reviewed. The opioid crisis is of utmost importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The total amount of opioid consumption (median [IQR]) after surgery until discharge was lower in the ERAS group than in the conventional group (MME, 44 mg vs 208 [146-294] mg; median difference, −143 mg; 95% CI, −154 to −132; P < .001; Table 3). The daily average opioid consumption was also lower in the ERAS group than in the conventional group (MME, 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] mg vs 39 [32-45] mg; median difference, −28 mg; 95% CI, −30 to −26; P < .001; Table 3). The number of patients discharged without an opioid prescription was higher in the ERAS group (156/260 [60%] vs 329/1860 [18%]; odds ratio, 7.0; 95% CI, 5.3-9.3; P < .001; Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The total amount of opioid consumption (median [IQR]) after surgery until discharge was lower in the ERAS group than in the conventional group (MME, 44 mg vs 208 [146-294] mg; median difference, −143 mg; 95% CI, −154 to −132; P < .001; Table 3). The daily average opioid consumption was also lower in the ERAS group than in the conventional group (MME, 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] mg vs 39 [32-45] mg; median difference, −28 mg; 95% CI, −30 to −26; P < .001; Table 3). The number of patients discharged without an opioid prescription was higher in the ERAS group (156/260 [60%] vs 329/1860 [18%]; odds ratio, 7.0; 95% CI, 5.3-9.3; P < .001; Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported decreased analgesic consumption and pain intensity in patients who received ERAS treatment compared to those who received conventional treatment. 6,[12][13][14] They used multidisciplinary analgesic protocols, such as thoracic epidural analgesia, paravertebral block, or postoperative ketamine infusion, to decrease postoperative opioid consumption, 6,[12][13][14] but these analgesic techniques also carry several risks and limitations. Furthermore, epidural and systemic strategies may be less appropriate for the majority of patients who underwent minimally invasive thoracic surgery for whom the pain may be less severe than after a thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations